2015
DOI: 10.1103/physrevb.92.144506
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced changes of the chemical potential in superconductingBi2Sr2CaCu2O8+δ

Abstract: The chemical potential of a superconductor is of critical importance since, at equilibrium, it is the energy where electrons pair and form the superconducting condensate. However, in non-equilibrium measurements, there may be a difference between the chemical potential of the quasiparticles and that of the pairs. Here we report a systematic time-and angle-resolved photoemission study of the pump-induced change in the chemical potential of an optimally doped Bi2Sr2CaCu2O 8+δ (Bi2212) sample in both its normal a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…[61] report a critical fluence near 40 µJ/cm 2 . We have found that an accurate measure of the onset for two-component dynamics can only be obtained after a careful treatment of pump-induced changes in the chemical potential [68], which may resolve this discrepancy.…”
Section: Figmentioning
confidence: 99%
“…[61] report a critical fluence near 40 µJ/cm 2 . We have found that an accurate measure of the onset for two-component dynamics can only be obtained after a careful treatment of pump-induced changes in the chemical potential [68], which may resolve this discrepancy.…”
Section: Figmentioning
confidence: 99%
“…The experimental methods are identical to those in Ref. [29]. Figure 1 establishes the procedure for finding ∆µ ε with TARPES, starting with an overdoped (OD) Bi2212 sample (T c ∼ 70 K), where the pseudogap is small or absent [30].…”
mentioning
confidence: 99%
“…However, as argued in Ref. [29], it is possible to change variables such that we consider the quasiparticle energy with the pairing interaction turned off. Under this change of variables, f (E − µ, T e ) is no longer a Fermi-Dirac distribution but now has an effective width w eff proportional to the size of the superconducting gap (∆ SC ) even at zero temperature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Energy, momentum, and time resolutions are 23 meV, 0.003Å −1 , and 300 fs. We have corrected for detector nonlinearity 27 , as well as for a pump-induced time-dependent but uniform energy shift in the electronic spectrum (≤ 4 meV) 36,38 . Figure 1 shows a fluence-dependent analysis of a nearly optimally doped sample (T c = 91 K), where two cuts through k-space are depicted, at φ = 45…”
mentioning
confidence: 99%